2010
DOI: 10.13073/0015-7473-60.4.309
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Impacts of a Domestic Phytosanitary Treatment Regulation for Wood Packaging Material Manufacturers

Abstract: The results of a mail survey undertaken in mid-2008 to determine the response of wood packaging material (WPM) manufacturers to a universal treatment requirement, similar to ISPM 15 “Guidelines for Regulating Wood Packaging Material in International Trade,” are described. Reactions to a universal requirement were positive (nearly 60% in favor), with larger companies tending to be more positive. Less than 9 percent of respondents indicated they would cease WPM manufacturing. Impacts on pallet pricing were most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…In recent times, significant pressures borne out of environmental concerns have risen from external sources including consumers and pressure groups, upstream and downstream supply chains, especially industrial customers and packaging producers, and the government (Corey and Bone, 1992;Kassaye and Verma, 1992;Labatt, 1997;Matthews, 2004;Verghese and Lewis, 2007;Dharmadhikari, 2012). The complexity of packaging decisions for industrial products have been further exacerbated by having to contend with legislation that decrees the packaging that is required for particular categories of products, such as explosives, fissile materials and foodstuffs, and even by the need to contend with subjects such as the elimination of pests and insects from wooden packaging materials (Molina-Murillo et al 2005;Slahor et al 2005;Chen et al 2006).…”
Section: Packaging Materials and Regulationsmentioning
confidence: 99%
“…In recent times, significant pressures borne out of environmental concerns have risen from external sources including consumers and pressure groups, upstream and downstream supply chains, especially industrial customers and packaging producers, and the government (Corey and Bone, 1992;Kassaye and Verma, 1992;Labatt, 1997;Matthews, 2004;Verghese and Lewis, 2007;Dharmadhikari, 2012). The complexity of packaging decisions for industrial products have been further exacerbated by having to contend with legislation that decrees the packaging that is required for particular categories of products, such as explosives, fissile materials and foodstuffs, and even by the need to contend with subjects such as the elimination of pests and insects from wooden packaging materials (Molina-Murillo et al 2005;Slahor et al 2005;Chen et al 2006).…”
Section: Packaging Materials and Regulationsmentioning
confidence: 99%
“…Não obstante a sua imprescindibilidade, a operacionalização do controle de medidas fitossanitárias podem impor problemas não somente ao MAPA, mas também a outros participantes envolvidos na atividade -cita-se, por exemplo, custos financeiros aos importadores (Hassler, Grushecky, Slahor, & Turk, 2010;Strutt, Turner, Haack & Olson, 2013;Leung, Springborn, Turner & Brockerhoff, 2014). Um componente destes custos é o custo de armazenagem do produto, e sua respectiva embalagem, em recintos alfandegados enquanto se aguarda o despacho aduaneiro pelos órgãos anuentes, dentre eles o MAPA.…”
Section: Introductionunclassified
“…Some of the major challenges relate to the lack of technical expertise and appropriate technologies, limited financial resources, the existence of incompatible production systems, and logistical problems (Henson, Brouder, & Mitullah, 2000). A case study by Hassler, Grushecky, Slahor, and Turk (2010) found that the implementation of ISPM 15 increased, on average, the cost of a single wood pallet by approximately 0.60 USD (with this amount varying across countries, depending on the technology and type of treatment adopted). The rise in the price of treated WPM (varying from country to country) increases the cost of traded goods and may change the set of comparative advantages a country has in particular sectors, hence creating winners and losers in international markets (Beghin & Bureau, 2001).…”
mentioning
confidence: 99%